2009
DOI: 10.1021/jp9075355
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in the Interaction of Electron Donor and Acceptor Molecules with Graphene and Single-Walled Carbon Nanotubes

Abstract: Interaction of electron donor and acceptor molecules with graphene samples prepared by different methods as well as with single-walled carbon nanotubes (SWNTs) has been investigated by isothermal titration calorimetry (ITC). The ITC interaction energies of the graphene samples and SWNTs with electron acceptor molecules are higher than those with electron donor molecules. Thus, tetracyanoethylene (TCNE) shows the highest interaction energy with both graphene and SWNTs. The interaction energy with acceptor molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 27 publications
6
57
0
1
Order By: Relevance
“…This is not surprising, given the fact that undoped graphene is electron rich due to the delocalized π (e -) charge cloud on it. This observation is consistent with the higher interaction energy of TCNE with graphene (FG) compared to TTF as measured calorimetrically [23].…”
Section: Resultssupporting
confidence: 86%
“…This is not surprising, given the fact that undoped graphene is electron rich due to the delocalized π (e -) charge cloud on it. This observation is consistent with the higher interaction energy of TCNE with graphene (FG) compared to TTF as measured calorimetrically [23].…”
Section: Resultssupporting
confidence: 86%
“…The increase in E ads observed for the adsorption of R-DMBI onto 555-777 defective graphene is accompanied by a larger charge transfer. In this sense, 8 we found that at the M06-L/6-31G* level, 0.87 e-are donated by R-N-DMBI. In the same line, Mulliken spin densities revealed that 1.0 e-is donated by R-N-DMBI.…”
Section: Resultssupporting
confidence: 48%
“…25 Adsorption of small organic molecules such as ethanol, acetone, acetonitrile, and toluene on the graphene surface has been studied both experimentally and theoretically. 27,28 Hybrid materials derived from graphene quantum dots exhibit excellent gas sensing ability. 27,28 Hybrid materials derived from graphene quantum dots exhibit excellent gas sensing ability.…”
Section: Introductionmentioning
confidence: 99%